Evolusie: Die misverstand tussen teologie en biologie - Van Dyk, P. J. (Hervormde teologiese studies, 1993)
Evolution: The misunderstanding between theology and biology Theological reaction to the theory of biological evolution ranged from an outright rejection to positive acceptance. Both these extreme viewpoints are, however, often mistaken in their basic assumptions. Rejection of evolution is often based on fundamentalist preconceptions th a t are both unnecessary and inconsistent with the Bible. On the other hand, acceptance of the theory of evolution is often based on an idealistic definition of evolution that is incongruous with the materialistic definition used by biologists.